2012
DOI: 10.5541/ijot.313
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Ammonia and Hydrogen Cyanide during Flameless Combustion of Low Calorific Value Gases

Abstract: In this paper, a review of the experimental investigations on the fuel-NO x formation during flameless combustion is presented. The first series of experiments described in the paper were conducted using ammonia doped synthetic gases with different compositions. During these experiments, the influence of gas composition on the conversion of ammonia (NH 3 ) to NO x is investigated. The second series of experiments were conducted using product gas generated in a fluidized bed gasifier. These results show the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Woo et al found that the fuel-NO x formation increases monotonically with increasing initial NH 3 concentration when pure oxygen is used as an oxidizer. Zieba et al , adopted a chemical reaction network to investigate the effects of CH 4 on fuel-NO x formation during flameless combustion with NH 3 as the nitrogen source. They found that the existence of CH 4 slows the oxidation of NH 3 , whereas NO x emissions increase.…”
Section: Introductionmentioning
confidence: 99%
“…Woo et al found that the fuel-NO x formation increases monotonically with increasing initial NH 3 concentration when pure oxygen is used as an oxidizer. Zieba et al , adopted a chemical reaction network to investigate the effects of CH 4 on fuel-NO x formation during flameless combustion with NH 3 as the nitrogen source. They found that the existence of CH 4 slows the oxidation of NH 3 , whereas NO x emissions increase.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a few ppm of ammonia on NO x formation during oxidation of biogas, natural gas, and syngas was explored by Zieba and coworkers , and Slefarski in a flameless burner. Results by these authors are summarized in Figure , where NO x concentration measured in the flues gases of a flameless burner have been reported.…”
Section: Biogas Conversion In Mild Combustionmentioning
confidence: 99%
“…In a very recent work by Sorrentino et al, the same trend has been obtained studying MILD combustion in methane/ammonia in a cyclonic burner in a wider range of NH 3 (from 0% to 100%). A kinetic analysis carried out on available models highlighted that the main backbone of the C and N oxidation mechanism proceed independently from each other and only compete for radicals. , …”
Section: Biogas Conversion In Mild Combustionmentioning
confidence: 99%
See 2 more Smart Citations